Banking Supervision : Quality and Governance - Gambini, Alessandro (IMF Working Papers; Working Paper ;, 2007)
This paper examines the relationship between the quality of banking supervision and governance of the supervisory agency, based on assessments of the Basel Core Principles and the IMF Code on Transparency in Financial Policies, covering 116 and 53 countries, respectively, with 51 common to both. We find a positive correlation between the transparency of the supervisor and the effectiveness of banking supervision; moreover, better accountability and integrity practices of the banking supervisors are associated with higher independence, which in turn is associated with better compliance with the Basel Core Principles. These results are largely robust to different stages of financial development.